Effect of Different Doses of Ge Citrate and Probiotic Lactobacillus casei B-7280 on the Phospholipid Composition of Bees Tissues - Pylypets, A.Z.; Kovalchuk, I.I.; Babenko, L.P.; Fedoruk, R.S.; Khymynets, T.M.; Tsap, M.M.; Romanovyсh, M.M.; Androshulik, R.L.; Zhylikhovska, T.V.; Пилипець, А.З.; Ковальчук, І.І.; Бабенко, Л.П.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Aim. To investigate changes in the phospholipid composition of bee body tissues under the influence of the lyophilized probiotic strain Lactobacillus casei IMV B-7280 in combination with nanotechnological Ge citrate in laboratory conditions. Methods. The research was conducted on honey bees of the Carpathian breed. Bees of the control group were fed with 60% sugar syrup in the amount of 1 cm3/group/day. Experimental 1 group of bees (E 1), in addition to 1 cm3 of sugar syrup, received 0.1 μg of Ge in the form of nanotechnological citrate and a solution of the probiotic L. casei B-7280 at a concentration of 106 CFU/cm3; experimental group 2 of bees (E 2), in addition to 1 cm3 of sugar syrup, received 0.2 μg of Ge in the form of citrate and L. casei B-7280 at a concentration of 106 CFU/cm3. Drinking sugar syrup, Ge citrate, and probiotics  lasted 34 days. In the preparatory period  and at the end of the experimental period, live bees were selected from the control and experimental groups for physiological and biochemical studies to determine the content of total phospholipids and the ratios of their classes in tissue homogenates of the entire organism. The content of total phospholipids was determined by the amount of inorganic phosphorus in the lipid extract. Thin-layer chromatography on silica gel was used to separate phospholipids. Rf values identified individual phospholipids. Quantitative analysis of phospholipid subclasses was performed using the TotalLab software, which was expressed as a percentage of total content. Results. The research results showed that in the homogenates of bee body tissues in the research groups, an increase in the content of total phospholipids was established relative to the preparatory period. In the fractional composition of phospholipids, an increase in the content of phosphatidylethanolamine and phosphatidylcholine was established in the tissues of bees of  groups E 1 and E 2 concerning the preparatory period. An increase in the content of phosphatidylethanolamine and phosphatidylcholine and a decrease in phosphatidylinositol in body tissue lipids of group E 2 compared to the control group were noted. A decrease in the content of phosphatidylinositol in the tissues of group E 2 bees relative to the preparatory period was also established. The content of sphingomyelin and lysophosphatidylcholine decreased in tissue lipids of bees of groups E 1 and E 2 as compared to the preparatory period. The use of lactobacillus casei strain B-7280 and Ge citrate led to an increase in the number of lactobacilli and bifidobacteria in both parts of the intestine, as well as to a decrease in the number of staphylococci, streptococci, and microscopic fungi. Conclusions. Nanotechnological Ge citrate and probiotic L.casei in the applied doses under the conditions of their feeding with sugar syrup in a laboratory thermostat for 34 days show a dose-dependent biological effect on honey bees by increasing the content of total phospholipids and changing the ratios of individual subclasses of phospholipids. However, it also indicates a shift in the spectrum of different fractions of phospholipids to a decrease in the content of hard-to-oxidize lysophosphatidylcholine and sphingomyelin while increasing easy-to-oxidize phosphatidylcholine and phosphatidylethanolamine, which may indicate stabilization of compensatory mechanisms for supporting cell membranes. The use of Lactobacillus casei B-7280 and Ge citrate for feeding bees under the conditions of the laboratory thermostat led to quantitative changes in the composition of the intestinal microbiota of bees, in particular to an increase in the number of lactic acid bacteria and bifidobacteria, as well as a decrease in the number of some other groups of microorganisms in the intestine.